Current Topics in Pharmacological Research on Bone Metabolism: Regulation of Bone Mass by the Function of Endogenous Modulators of Bone Morphogenetic Protein in Adult Stage - Masaki Noda (Elsevier, 2006)
Abstract.: Bone formation in adults determines the basic mass of bone and hence it is crucial to understand the mechanisms of its regulation. As remodeling is proceeding, bone resorption is determined by the physical conditions. Especially in women, postmenopausal bone loss is characterized by rapid bone loss due to increase in bone resorption and relative negative balance between such bone resorption and accelerated bone formation. Bone formation is also critical in considering measures to treat patients with very low bone mass. In these subjects, simple suppression of bone resorption would not be enough to maintain bone mass. Thus, bone formation in the adult is of importance in terms of both pathological and therapeutic aspects. This review addresses the possible roles of bone formation modulators in the maintenance of bone mass in the light of understanding the determination of adult bone mass. Keywords:: bone mass, bone morphogenetic protein, bone resorption, bone formation, Tob